Planning for success: Full mouth rehabilitation with different fixed restorations - Bin Fadly Loo, Muhamad Faizran Loo Szen (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: A minimally invasive approach in a full mouth rehabilitation is preferred, especially in a younger patient, as it is reversible, in line with the European Consensus Statement. Purpose: This case report aims to highlight the importance of detailed planning of a full mouth rehabilitation involving different fixed restorations, including direct composite restoration, indirect posterior onlays, and the replacement of an unrestorable tooth with a dental implant. Case: A 52-year-old gentleman presented with severe generalized non-carious tooth surface loss (NCTSL), planned for full mouth rehabilitation in a reorganized approach. His treatment was complicated by subgingival restorative margins and an unrestorable tooth, requiring replacement. Case management: Periodontal disease was stabilized, and the full mouth rehabilitation was initiated with direct composite restoration of the anterior teeth using the injection molding technique (IMT), followed by the implant placement protocol and extraction of unrestorable tooth 24. The final implant abutment and restoration were digitally designed and delivered with high accuracy. Conclusion: Full mouth rehabilitation requires detailed planning and can be complicated by the replacement of missing teeth with dental implants. However, digital technology and good communication with the dental technologist can help to deliver the prosthodontically driven implant restoration with good accuracy.